EFFECT OF WONDERFUL KOLA SEED MEAL (Buccholzia coriacea) ON GROWTH, MASCULINIZING POTENCY AND GONAD GROSS MORPHOLOGY OF THE NILE TILAPIA (Oreochromis niloticus, LINNAEUS 1758) - Felix Eze; Eyo Victor Oscar (Department of Aquaculture, 2019)
This study was aimed to investigate the effect of Buchholcia coriacea on the masculinization of Oreochromis niloticus. Five days old mixed sex of O. niloticus (mean weight 0.2g, mean length 0.45mm) were subjected to powdered B. coriacea seeds meal (BSM) at 0, 2, 4, 6, 8, 10g/kg twice daily for 1 month in an indoor experimental plastic basin capacity (50cm in diameter and 30cm deep) in duplicates with a total of six treatments in a complete randomized design. After which there were later fed with a normal diet in an outdoor concrete tank of size 1m3 for another one month. One way ANOVA and LSD were used to analyze the experimental data. The result obtained in this study showed that fish fed with 4g/kg BSM powdered BSM had the highest number (83.33%) of males which was significantly higher (p<0.05) compared to all other treatments categories. The highest survival rate (100%) was recorded in fish fed with 6g/kg BSM. The highest mean length, mean weight and weight gain observed are 0.488mm, 4.68g, and 4.65g respectively. The result of the histology showed that B. coriacea altered the sex of O. niloticus due to the presence of a hormone called dopamine in the kola. Conclusively, B. coriacea showed potential reproduction control in Oreochromis niloticus.